Defining a screening tool for post-traumatic stress disorder in East Africa: a penalized regression approach - Meffert, Susan M.; Mathai, Muthoni A.; Ongeri, Linnet; Neylan, Thomas C.; Mwai, Daniel; Onyango, Dickens; Akena, Dickens; Rota, Grace; Otieno, Ammon; Obura, Raymond R.; Wangia, Josline; Opiyo, Elizabeth; et al. (Frontiers in Public Health, 2024)
Background Scalable PTSD screening strategies must be brief, accurate and capable of administration by a non-specialized workforce. Methods We used PTSD as determined by the structured clinical interview as our gold standard and considered predictors sets of (a) Posttraumatic Stress Checklist-5 (PCL-5), (b) Primary Care PTSD Screen for the DSM-5 (PC-PTSD) and, (c) PCL-5 and PC-PTSD questions to identify the optimal items for PTSD screening for public sector settings in Kenya. A logistic regression model using LASSO was fit by minimizing the average squared error in the validation data. Area under the receiver operating characteristic curve (AUROC) measured discrimination performance. Results Penalized regression analysis suggested a screening tool that sums the Likert scale values of two PCL-5 questions—intrusive thoughts of the stressful experience (#1) and insomnia (#21). This had an AUROC of 0.85 (using hold-out test data) for predicting PTSD as evaluated by the MINI, which outperformed the PC-PTSD. The AUROC was similar in subgroups defined by age, sex, and number of categories of trauma experienced (all AUROCs>0.83) except those with no trauma history- AUROC was 0.78. Conclusion In some East African settings, a 2-item PTSD screening tool may outperform longer screeners and is easily scaled by a non-specialist workforce.